Pelatihan Sitasi dan Referensi dengan Aplikasi Manajemen Referensi - Sutoyo, Muh. Nurtanzis; Sapriyadi; Iin, Johar Nur; Murhaban, Murhaban; Utomo, Pradityo (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
This workshop seeks to improve participants' comprehension and proficiency in the appropriate management of citations and references. The exercises encompass an introduction to fundamental citation concepts, the significance of precision in bibliographies, and the practical implementation of tools such as Mendeley and Zotero. The training approach consists of theoretical instruction and practical application, culminating in assessment via a final assignment. The training outcomes demonstrate an enhancement in participants' comprehension of diverse citation forms, including APA, MLA, and IEEE, alongside their proficiency in importing, managing, and automatically compiling references. The majority of participants successfully employed the programs' functionalities to facilitate collaborative research efforts. The documentation of activities via Zoom Meetings indicates active engagement from the trainees during the sessions. The instruction effectively enhanced participants' efficiency in the academic writing process. This course aims to serve as a prototype for such programs in the future to improve the quality of academic papers.